Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702501
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Muscle-Computer Interfaces with High-Density Electromyography

Abstract: In this paper we present our results on using electromyographic (EMG) sensor arrays for finger gesture recognition. Sensing muscle activity allows to capture finger motion without placing sensors directly at the hand or fingers and thus may be used to build unobtrusive body-worn interfaces. We use an electrode array with 192 electrodes to record a highdensity EMG of the upper forearm muscles. We present in detail a baseline system for gesture recognition on our dataset, using a naive Bayes classifier to discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 22 publications
2
113
0
Order By: Relevance
“…Features extracted from HD-sEMG maps can be based on intensity information (any signal magnitude and power feature [18,22]) and spatial information (e.g., the mean shift [42] or the coordinates of the centre of gravity and maximum values [44]). These maps and additional spatial-based features can be used to reduce the effect of confounding factors that influence the performance of EMG pattern recognition such as the changing characteristics of the signal itself over time and electrode location shift [45] as well as variations in muscle contraction intensity [44]. However, this remains a relatively new sub-field, and novel image segmentation and spatial feature extraction methods are still needed to improve the performance of robust EMG pattern recognition.…”
Section: High-density Surface Emgmentioning
confidence: 99%
See 1 more Smart Citation
“…Features extracted from HD-sEMG maps can be based on intensity information (any signal magnitude and power feature [18,22]) and spatial information (e.g., the mean shift [42] or the coordinates of the centre of gravity and maximum values [44]). These maps and additional spatial-based features can be used to reduce the effect of confounding factors that influence the performance of EMG pattern recognition such as the changing characteristics of the signal itself over time and electrode location shift [45] as well as variations in muscle contraction intensity [44]. However, this remains a relatively new sub-field, and novel image segmentation and spatial feature extraction methods are still needed to improve the performance of robust EMG pattern recognition.…”
Section: High-density Surface Emgmentioning
confidence: 99%
“…In fact, several studies have shown that there is little need to use all EMG channels (over 100 electrodes), and instead, a properly positioned smaller set of electrodes (e.g., 9 [44] and 20-80 [45]) can provide comparable results. There is, however, no consensus on the global optimum number of electrodes yielding maximum recognition performance.…”
Section: High-density Surface Emgmentioning
confidence: 99%
“…EMG sensors can recognize muscle activities. Amma et al [8] presented their results on using EMG sensor arrays for finger gesture recognition. However, changes in the EMG sensor values are small, and EMG sensors are adversely affected by electrical noise.…”
Section: Gesture Recognition Methodsmentioning
confidence: 99%
“…We performed fast Fourier transform (FFT) on the input from the contact microphone. In this study, the sampling rate was 96 kHz, and the number of FFT samples was 8,192. As shown in Fig.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation